Effectiveness Of Application Of Management Accounting Information Model In Village Fund Management For Empowerment Of Business Activities In Kabila Bone District, Bone Bolango Regency, Gorontalo Province - Mattoasi MATTOASI; Sutan Muhammad RAIHAN; Suryadi MADJID (Indonesia Strategic Sustainability, 2022)
This study relates to the model of applying management accounting information in managing village funds for economic empowerment in the community. This study aims to determine the model of the application of management accounting information in maximizing the management of village funds. The research method is based on qualitative methods, relying on method and source triangulation to answer the problem formulation. The results showed that the accounting information model used by the village government in Kabila Bone District was ineffective because the model did not require regular reports and periodic reports from business actors during the implementation of activities. Hence, it greatly affected the management of village funds to empower the community for the next stage.